Optimization of Microwave Ultrasound Extraction of Biopolymer from using Response Surface Methodology - Rahmawati, Istiqomah; Annisa, Yasmin; Farwah, Zilma Aliyah; Adrian, Febri; Anggraini, Ranita Anggi; Fachri, Boy Arief; Reza, Muhammad; Rizkiana, Meta Fitri; Palupi, Bekti; Amini, Helda Wika (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2023)
This study aims to determine the effect of combining the two extraction methods Microwave Assisted Extraction (MAE) and Ultrasound-Assisted Extraction (UAE) on the yield and content of ulvan polysaccharides from Ulva lactuca with the best operation condition. Algae biomass U. lactuca is abundant, according to its content, U. lactuca contains polysaccharides which can be used as biodegradable plastic materials. The extraction was carried out using Microwave Ultrasound Extraction by varying the microwave power from 100 to 800 watts, the microwave time variations from 10 to 50 minutes, the ultrasonic wave temperature range from 40-80 oC, and the ultrasonic wave time variations from 20 to 50 minutes. Optimization was performed using the response surface methodology center composite design methodology for a total of 28 runs. Several tests were carried out to determine the character of the ulvan polysaccharide, including water content, FT-IR spectroscopy, High-Performance Liquid Chromatography, and its antioxidant activity. The effect of combining Microwave Assisted Extraction (MAE) and Ultrasound-Assisted Extraction (UAE) provides an optimal extraction condition with higher yields and good quality ulvan.